SEDAYU BEACH, NORTH LOMBOK REGENCY: STRATEGIES TO INCREASE TOURIST VISITS - Wijaya, Zaradiska Mutiara; Singandaru, Adhitya Bagus; Budiatiningsih, Mahmudah (Journal of Finance, Economics and Business, 2024)
The objective of this scientific paper is to examine and identify effective strategies for increasing the number of tourist visits to Sedayu Beach Tourism Object, North Lombok Regency. This research employs the SWOT analysis method to evaluate the strengths, weaknesses, opportunities, and threats faced by tourist destinations. The findings of the SWOT analysis provide the foundation for the development of marketing strategies, infrastructure, and tourist services that can enhance the appeal of Sedayu Beach. Furthermore, the research involved local residents, tourism stakeholders, and other relevant parties in the decision-making process. The findings of this research indicate the potential of Sedayu Beach, which serves as a protected habitat for the endangered green turtle. The strategies proposed to increase tourist visits to Sedayu Beach are as follows: The following strategies have been proposed for the development of Sedayu Beach: 1) The breeding of turtles and collaboration with the Department of Marine Affairs and Fisheries; 2) The provision of camping equipment in the beach area; 3) Education and awareness about the actions that must be taken when an earthquake occurs; 4) The development of green and environmentally friendly transportation; 5) The increase of tourism promotion and collaboration with the community and related agencies; 6) The conduction of socialisation related to disaster prone areas; and 7) The organisation of an activity or event related to local culture. The results of the SWOT analysis indicate that, while Sedayu Beach still faces shortcomings and threats, these can be addressed by leveraging the opportunities and strengths of the tourism sector as a strategy for increasing tourist visits to the beach. Keywords: Strategies to increase visits, tourists, Sedayu Beach